Applying the Means of Crossword Game to Increase Vocabulary Memorization in Teaching Arabic Language Among Middle School Students "Jannaturroichan " Peterongan Jombang - Nur Alfiyatus Sholichah; Lailatul Qomariyah (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2024)
Arabic is a language that is difficult to learn because of the minimal methods teachers use when teaching, or the difficulty of students focusing when learning Arabic. For this reason, effective teaching media is needed in Arabic language lessons. This research aims to determine the application of crossword puzzle game media to improve vocabulary memorization in teaching Arabic to students at "Jannaturroichan" Middle School in Peterongan Jombang. Therefore, this research applies the crossword puzzle game media. The research method used is descriptive qualitative research with a case study approach. The qualitative approach focuses on the design, use, management, and evaluation stages, as well as data collection through interviews, observations, and documentation, research reveals that crossword puzzle media in Arabic language teaching has supporting and inhibiting factors. The supporting factors are the quality of teachers who are educative, innovative, and have teaching certificates. And the inhibiting factors are students who lack motivation so they are not enthusiastic about learning Arabic. This study also found that the media of crossword games in teaching Arabic can increase students' enthusiasm for learning because the learning process is exciting and not boring. In this study, the researcher wants to share experiences in the application of crossword game media in teaching Arabic to increase students' vocabulary.Keywords: Cross gaming, Descriptive qualitative, Improved Arabic language